2007
DOI: 10.1007/s00280-007-0628-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the growth inhibition and apoptosis effect of mifepristone (RU486) in human Ishikawa and HEC1A endometrial cancer cell lines

Abstract: Mifepristone demonstrates activity in both HEC-1-A and Ishikawa cells at clinically relevant concentrations based on an oral human dose of about 200 mg/day. While its mechanism of action remains unknown, this data supports an increase in apoptosis that may be due to p53 activation rather than hormone receptor mediation. Additional studies are needed to help further identify mifepristone mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Since the first clinical trial in 1982, RU486 has been used in many clinical studies in the gynecologic fields including endometrial cancer (Schneider et al 1998). Navo et al (2008) have tested RU486 in Hec-1-A and Ishikawa cell lines and upon treatment with RU486, PR expression increased in Hec-1-A cells with no change in ERa/b levels. Moreover, the expression of p53 and Cox-2 increased and Bcl-2 decreased in this set of experiments.…”
Section: Progesterone and Progesterone Receptorsmentioning
confidence: 99%
“…Since the first clinical trial in 1982, RU486 has been used in many clinical studies in the gynecologic fields including endometrial cancer (Schneider et al 1998). Navo et al (2008) have tested RU486 in Hec-1-A and Ishikawa cell lines and upon treatment with RU486, PR expression increased in Hec-1-A cells with no change in ERa/b levels. Moreover, the expression of p53 and Cox-2 increased and Bcl-2 decreased in this set of experiments.…”
Section: Progesterone and Progesterone Receptorsmentioning
confidence: 99%
“…Mifepristone was also found to increase the sensitivity of chemotherapies for gastric cancer, breast cancer, endometrial cancer, and leukemia (Gaddy et al, 2004;Li et al, 2004;Check et al, 2007;Navo et al, 2008). Its mechanisms may include: 1) blocking ceramide glycosylation and promoting cell apoptosis; 2) reducing exocytosis of MDR-associated proteins and P-glycoprotein while elevating the intracellular drug concentration; 3) enhancing the DNA repair capacity and changing the activity of topoisomerase II and the expression of tumor suppressor genes such as p53.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that mifepristone has a dose-dependent in vitro inhibitory effect on endometrial cancer cell lines and can reduce the myometrial volume in benign leiomyoma. [14][15][16][17] Although, the mechanism of inhibition is unknown, the regulation of PR concentration through vascular alterations of the endometrium and manipulation of p53 have been reported. 15,18,19 This, this information served as a basis for the design of the current trial.…”
mentioning
confidence: 99%
“…25,26 This SPRM action partially explains the growth-inhibitory effect of mifepristone on endometrial cancer cell lines. 15,16 Its primary abortifacient effect, however, is caused by the antiprogesterone and associated prostaglandin (PG)-inducing effects. It is believed that mifepristone sensitizes the uterus to PGs and, when administered in the first trimester of pregnancy at a single dose of 600 mg, causes pregnancy termination.…”
mentioning
confidence: 99%
See 1 more Smart Citation